CO Multi-line Imaging of Nearby Galaxies (COMING). IV. Overview of the project. (19th November 2019) - Sorai, Kazuo; Kuno, Nario; Muraoka, Kazuyuki; Miyamoto, Yusuke; Kaneko, Hiroyuki; Nakanishi, Hiroyuki; Nakai, Naomasa; Yanagitani, Kazuki; Tanaka, Takahiro; Sato, Yuya; Salak, Dragan; Umei, Michiko; et al.
Abstract: Observations of the molecular gas in galaxies are vital to understand the evolution and star-forming histories of galaxies. However, galaxies with molecular gas maps of their whole discs at sufficient resolution to distinguish galactic structures are severely lacking. Millimeter-wavelength studies at a high angular resolution across multiple lines and transitions are particularly needed, severely limiting our ability to infer the universal properties of molecular gas in galaxies. Hence, we conducted a legacy project with the 45 m telescope of the Nobeyama Radio Observatory, called the CO Multi-line Imaging of Nearby Galaxies (COMING), which simultaneously observed 147 galaxies with high far-infrared (FIR) flux in 12 CO, 13 CO, and C 18 O J = 1–0 lines. The total molecular gas mass was derived using the standard CO–to–H2 conversion factor and found to be positively correlated with the total stellar mass derived from the WISE 3.4 μm band data. The fraction of the total molecular gas mass to the total stellar mass in galaxies does not depend on their Hubble types nor the existence of a galactic bar, although when galaxies in individual morphological types are investigated separately, the fraction seems to decrease with the total stellar mass in early-type galaxies and vice versa in late-type galaxies. No differences in the distribution of the total molecular gas mass, stellar mass, or the total molecular gas to stellar mass ratio was observed between barred and non-barred galaxies, which is likely the result of our sample selection criteria, in that we prioritized observing FIR bright (and thus molecular gas-rich) galaxies.